Vestibular cognition: State-of-the-art and future directions. Issue 7 (16th November 2020) - Ferrè, Elisa Raffaella; Haggard, Patrick
ABSTRACT: Vestibular information has been traditionally considered as a specialized input for basic orienting behaviours, such as oculo-motor adjustments, postural control and gaze orientation. However, in the past two decades a widespread vestibular network in the human brain has been identified, that goes far beyond the low-level reflex circuits emphasized by earlier work. Because this vestibular cortical network is so widely distributed, it could, in principle, impact multiple neurocognitive functions in health and disease. This paper focuses on the relations between vestibular input, vestibular networks, and vestibular interventions by providing the authors' personal viewpoint on the state-of-the-art of vestibular cognitive neuropsychology, and its potential relevance for neurorehabilitation.